Datos Sobre el Magnesio - Jennifer Hillan; Linda B. Bobroff (EDIS)
This 3-page fact sheet describes the importance of the mineral magnesium in human health, including recommended intakes and food sources. It is a minor revision written by Jennifer Hillan and Linda B. Bobroff, and published by the Department of Family, Youth and Community Sciences, October 2017.